Tira los libros, sal a la calle: el concepto de taishū de Yoshimoto Takaaki y la concepción del cine de Terayama Shūji - de Vargas, Ferran (El Colegio de México, 2018)
A knowledge of an ideology’s artistic aspect facilitates the understanding of its theory, and vice versa. This article makes a com-parative analysis of the film-making of Terayama Shūji, specifically Sho o suteyo machi e deyō [Throw away your books, rally in the streets], and Yoshimoto Takaaki’s theory of taishū, both as components of the Japanese New Left’s ideology of the late 1960s and early 1970s. Specifically, I focus on the parallels between Terayama’s films and Yoshimoto’s theory in their view of the relationship between the intellectual and the masses. I develop this comparative analysis on the basis that, even though both Yoshimoto and Terayama criticize ideology, their proposals contain a strong political component.